2018
DOI: 10.1007/s42770-018-0025-2
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli O157:H7 by ozone in different substrates

Abstract: Ozone has a broad antimicrobial spectrum and each microorganism species has inherent sensitivity to the gas. The objective of this study was to evaluate the effect of ozone gas on Escherichia coli O157:H7 inoculated on an organic substrate, and the efficacy of ozonated water in controlling the pathogen. For the first experiment, E. coli O157:H7 (ATCC® 43890™) was inoculated in milk with different compositions and in water, which was ozonated at concentrations of 35 and 45 mg L −1 for 0, 5, 15, and 25 min. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Supported by previous studies, a concentration of 0.25 mg.l -1 of dissolved ozone in water has a disinfecting effect of 99.99 % particularly on E. coli [14]. This level was reached after 120 min of ozonisation in distilled water, but not in potable water that required more than 120 min of ozonisation with G1, and was slightly exceeded after 150 min (0.26 mg.l -1 ).…”
Section: Ozone Generator G1mentioning
confidence: 64%
See 1 more Smart Citation
“…Supported by previous studies, a concentration of 0.25 mg.l -1 of dissolved ozone in water has a disinfecting effect of 99.99 % particularly on E. coli [14]. This level was reached after 120 min of ozonisation in distilled water, but not in potable water that required more than 120 min of ozonisation with G1, and was slightly exceeded after 150 min (0.26 mg.l -1 ).…”
Section: Ozone Generator G1mentioning
confidence: 64%
“…Results of ozonisation of potable and distilled water at 20 °C showed that the increase in O 3 level during ozonisation with G1 was more rapid in distilled water where the concentration of 0.25 mg.l -1 , that should be effective against E. coli [14], was reached after 120 min while in potable water after 150 min. Initial pH of this potable water (MC) a was 7.59 and of distilled water 7.06 and initial conductivity of potable water was 43.9 mS.m -1 and of distilled water 2.4 mS.m -1 .…”
Section: Discussionmentioning
confidence: 99%
“…de Oliveira Souza et al. (2019) obtained a maximum detectable reduction in the population of E. coli upon ozone exposure in distilled water as compared to different milk formulations indicating the AO is an effective approach for controlling microbial contamination with regard to food safety.…”
Section: Factors Influencing Inactivation Efficiency Of Ozonementioning
confidence: 98%
“…5A; Additional file 2: Table S1). Of these genes, 17 S1). Under low dose, several of these biofilm-associated genes were upregulated during the first and second hours, and then subsequently downregulated during the third hour.…”
Section: Effects Of O 3 On Genes Associated With Pathogenicity Stress Response and Defensesmentioning
confidence: 99%
“…Strategies including on-farm hygiene, decontamination by washing, film coating, prophage induction, and the use of chemical interventions that involve sodium hypochlorite (NaClO), sodium chlorite (NaClO 2 ), acidified NaClO 2 , acidified sodium benzoate (NaB), or peracetic acid (PAA) are common means for post-harvest control of bacterial contamination on fresh tomatoes and other types of vegetables [12][13][14]. Ozone gas (O 3 ) has been widely used decontaminating agent for eliminating E. coli O157:H7 and L. monocytogenes on various types of surfaces, including seeds, fresh fruits, as well as other organic and inorganic substrates such as milk and water [15][16][17][18]. However, the long-term impacts of such chemical intervention to potential acclimation, adaptation, and selection caused by chronic exposure to selective doses are often overlooked.…”
Section: Introductionmentioning
confidence: 99%